Assessing the content validity of the Physical Therapy Competence Assessment for Airway Suctioning (PT-CAAS) in chronic and community care settings. Issue 2 (4th March 2022) - Miller, Erin; Mori, Brenda; Nonoyama, Mika; Vaza, Pankaj; Brooks, Dina
Abstract: RATIONALE: Given that airway suctioning is a higher-risk treatment technique, it is important to assess the competence of health care professional that perform it. OBJECTIVES: The objectives of this study were to describe how patients, caregivers and health care professionals in chronic and community care settings define the construct of competence for airway suctioning, and to assess the content validity of the Physical Therapy Competence Assessment for Airway Suctioning (PT-CAAS) from the perspective of these key stakeholders. METHODS: A qualitative descriptive study using one-on-one semistructured interviews was the method used for this research. Participants were purposefully recruited from the chronic and continuing care units of a health care center in Toronto, Canada, as well as from the community. Directed content analysis was used to interpret meaning from interview data. Data related to definitions of competence for airway suctioning were coded using knowledge, skills and judgment as the initial coding categories. MEASUREMENTS AND MAIN RESULTS: Eleven individuals participated in the study, including 1 patient, 2 caregivers, 5 respiratory therapists, 2 physical therapists and 1 registered practical nurse. The majority of elements included in participants' definitions of competence for airway suctioning were well aligned with elements in the PT-CAAS and our initial coding categories. A prominent theme we were unable to capture with our initial coding scheme was the importance of confidence. The PT-CAAS was found to be comprehensive and relevant for use with physical therapists who perform airway suctioning with adults. CONCLUSIONS: This study provides evidence in support of the PT-CAAS's content validity.